The Strategic Planning in Indonesia Tourism Industry With QSPM Model - Jumadi, Jumadi; Bakri, Samsul; Stevina, Savira Devi (Eximia, 2022)
This study aims to provide strategic assessment and optimization strategies for the development of the tourism industry in Indonesia. The study contributes to development methodology by advancing uses techniques; Quantitative Strategic Planning Matrix (QSPM) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) to determine necessary guidelines for the development of tourism in Indonesia. The study first uses SWOT to categorize different factors and then QSPM is applied to prioritize various factors. Based results of this study show that presenting, formulated an alternative strategy in Indonesia tourism industry are Branding Indonesia tourism destination, satisfaction tourism strategy, tourism-based heritage, and culture, building the optimization of promotion with government support, human and technology development, developing public transportation and safety facilities of tourism, the complete package of several facilities options and development tourist attractions such as art and culture performances.